Pengaruh Jabatan Fungsional Auditor dan Motivasi Kerja Terhadap Kinerja Auditor Inspektorat Jenderal Kementerian Perhubungan - Teguh Pribadi (Jurnal Syntax Transformation, 2022)
The purpose of this study was to determine the functional position and work motivation affect the performance of auditors at the Inspectorate General of the Ministry of Transportation. The method used in this study is a descriptive method to get a clear picture of the Functional Position and Work Motivation on the Auditor's work through a questionnaire represented by a specified sample of 40 people. Data collection techniques used are field data collection techniques by means of interviews and questionnaires. Then the data that has been collected is processed using product moment correlation analysis and regression analysis. The results of the product moment correlation analysis show that functional positions affect the performance of auditors in the medium group (rx1y = 0.554) while the work motivation of employees in the medium group with results (rx2y = 0.445). While the results of the regression analysis showed a positive and significant effect and obtained t count 4.10 and t table 2.021. Thus, functional positions have a strong influence on the performance of the auditors of the Inspectorate General of the Ministry of Transportation, while the results of the regression analysis can show a positive and significant effect with t count 0.92 and t table 2.021 and it can be said that work motivation has a moderate influence on the performance of the inspectorate auditors. General of the Ministry of Transportation.